Relationship of Asymmetrical Dimethylarginine, Nitric Oxide, and Sustained Attention during Attack in Patients with Major Depressive Disorder - Serpil Canpolat; İsmet Kırpınar; Erdem Deveci; Hülya Aksoy; Zafer Bayraktutan; İbrahim Eren; Recep Demir; Salih Selek; Nazan Aydın (The Scientific World Journal)
We investigated the relationship of serum nitric oxide (NO) and asymmetrical dimethylarginine (ADMA) levels with cognitive functioning in patients with major depressive disorder (MDD). 41 MDD patients (Beck depression scale scores >16) and 44 controls were included in the study. Rey verbal learning and memory test, auditory consonant trigram test, digit span test, Wisconsin card sorting test, continuous performance task (TOVA), and Stroop test scores were found to be impaired in patients with major depressive disorder when compared to healthy controls. There was no significant difference between patient and control groups in terms of serum NO and ADMA. Serum NO levels were correlated with TOVA test error scores and Stroop test time scores, whereas serum ADMA levels were negatively correlated with TOVA test error scores. Metabolic detriments especially in relation to NO metabolism in frontal cortex and hypothalamus, psychomotor retardation, or loss of motivation may explain these deficits.